Secondary Cleft Nasal Deformity Correction Using Bioabsorbable Mesh. Issue 5 (July 2016) - Kim, Jeenam; Kim, Junyeong; Uhm, Ki-il; Shin, Donghyeok; Kim, Soonheum; Kim, Cheolkeun; Jo, Dongin; Choi, Hyungon
Abstract : Introduction: Septorhinoplasty in cleft patients is relatively difficult to perform and the outcomes are often unsatisfactory owing to weakness of the cartilage. Therefore, providing support to the cartilage is necessary. The authors used bioabsorbable mesh as a spreader or batten graft to support the septum in cleft patients those with weak cartilages. The purpose of this study was to evaluate the efficacy of bioabsorbable mesh when performing septorhinoplasty in cleft patients. Methods: Between 2009 and 2013, 34 patients with cleft lip and nose underwent open septorhinoplasty by using bioabsorbable mesh at the Konkuk University Medical Center. The authors determined the nasolabial angle, Goode ratio, alar base-nasal tip-columellar base angle, and columellar axis angle and performed a panel evaluation. Results: In all, 29 of the 34 patients were included; 5 patients were excluded as lost to follow-up. The nasolabial angle increased from 85.69° to 91.62° ( P  = 0.0032), and the mean Goode ratio increased from 0.51 to 0.55, which was approximately the ideal value ( P  = 0.0017). The alar base-nasal tip-columellar base angle decreased from 36.28 to 31.74 ( P  < 0.0001). The columellar axis angle increased from 82.36 to 86.90 ( P  < 0.0001). Discussion: As bioabsorbable mesh can provide strong support, results in good esthetic outcomes, and causes minimal complications, it can be used in septorhinoplasty for cleft patients.